A study on a novel solar contribution evaluation method for the solar-aided coal-fired power generation system - Jiang, Yue; Duan, Liqiang; Tong, Yongjing; Yang, Ming; Pang, Liping (Frontiers in Energy Research, 2022)
Solar-aided coal-fired power generation (SACPG) technology is an effective method of solar energy utilization. It could balance the demand of carbon dioxide emission reduction and renewable energy efficient power generation and promote carbon peaking and carbon neutralization. Accurate analysis of the share of solar energy in the unit output power could benefit the selection of the best integration scheme and exploitation of solar energy for further research. A novel solar contribution evaluation method of an SACPG system is put forward. The exergy is taken as the evaluation benchmark, and the method can be applied in an SACPG system with multiple integration positions with solar energy. The solar energy input from different positions in the system is analyzed separately. The solar energy input positions and the impact of solar exergy destruction on the solar energy contribution are considered. The proposed method also analyzes the flow direction and destruction of each solar exergy in different parts of the SACPG system and expresses the solar contribution in the electricity generated by each stage steam turbine in the form of a theoretical formula. Ultimately, the solar exergy contribution in the whole SACPG system is calculated by accumulating each result. Furthermore, the new method is applied to a tower solar-aided coal-fired power generation (TSACPG) system with thermal energy storage (TES) for comparative analysis. Compared with other solar contribution evaluation methods, the comprehensiveness and accuracy of the novel method are analyzed. Meanwhile, the exergy destruction distributions of the TSACPG system are revealed. The method can also be further used to excavate the application potential of solar energy in coal-fired units and provide theoretical support for highly efficient utilization of solar energy.